(untitled) (Bangladesh Journal of Agriculture, 2023)
Climate smart agriculture (CSA) is highly knowledge-intensive and innovative by nature. This study therefore aims to assess the extent of knowledge of coastal farmers on CSA and explore the contributions of the selected characteristics of the coastal farmers to their knowledge. Data were collected by using an interview schedule from 354 coastal farmers of 3 districts namely, Satkhira, Khulna, and Bagerhat through Multistage Random Sampling Method during December 2021 to March 2022. Descriptive and inferential statistics were applied. To explore the contribution of the predictor variables to the outcome variables, full model regression analysis was employed. Results indicate that about 14.13% of the farmers had poor knowledge, 75.14% had medium-level knowledge and the rest 10.73% had high level knowledge on CSA. Farmers’ education, annual agricultural income, extension contact, decision making ability and benefit obtained from CSA had positive significant contributions to their knowledge on CSA. The findings show that CSA approaches are more likely to be knowledge-rich than technology-intensive. Bangladesh J. Agri. 2023, 48(2): 63-74